Sex allocation - West, Stuart A., 1970- (Monographs in population biology, 2009)
Recent decades have witnessed an explosion of theoretical and empirical studies of sex allocation, transforming how we understand the allocation of resources to male and female reproduction in vertebrates, invertebrates, protozoa, and plants. In this landmark book, Stuart West synthesizes the vast literature on sex allocation, providing the conceptual framework the field has been lacking and demonstrating how sex-allocation studies can shed light on broader questions in evolutionary and behavioral biology. West clarifies fundamental misconceptions in the application of theory to empirical data.